KERAGAAN AGROINDUSTRI BERAS SIGER (KASUS DI AGROINDUSTRI TOGA SARI KABUPATEN TULANG BAWANG DAN AGROINDUSTRI MEKAR SARI KOTA METRO) - Sheila Fathia Aldhariana; Dyah Aring Hepiana Lestari; Hanung Ismono (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
The purpose of this research are to determine the process of raw materials procurement that correspond to six right(on time, right place, right quality, right quantity, right type, and the right price), to analyze processing activities to make income and added value of products, to determine the marketing mixin the marketing activities of siger rice’s product, andto determine the role of supporting services.  This research uses a case study method in Toga Sari Agro industryat Wira Agung Sari Village, Penawartama Tulang Bawang and in Mekar Sari Agro industryat Margorejo Village, South Metro Metro City. The research locations are chosen purposively by consideration of comparing both agro industry based on the similarities and differences they have.  Data of this research was collected on August 2015 – November 2015 and be analyzed by descriptive analysis of quantitative and qualitative.  The result of this research showed that the sixth component of raw materials procurement in Toga Sari Agro industry has been right, while in Mekar Sari Agro industry there was one component, namely price, has not been right. The income in Toga Sari Agroindustry was bigger than that of in Mekar Sari Agroindustry.  Both siger rice’s agro industries were viable because they had positive added value and quite favorable seen by the R/C ratio.   Marketing strategy of siger rice in both agro industries have been using marketing mix. All of supporting services were utilized in Toga Sari and Mekar Sari Agroindustry gave a positive role for the continuity of the production activities.Key words: agroindustry, marketing, siger rice